A case of sclerosing odontogenic carcinoma. Issue 6 (November 2021) - Seki, Soju; Tanaka, Susumu; Hara, Takayuki; Nishimura, Nao; Oya, Kaori; Uchihashi, Toshihiro; Hiraoka, Shinichiro; Hamaguchi, Munehiro; Kogo, Mikihiko
Abstract: Sclerosing odontogenic carcinoma is a rare, locally destructive neoplasm that is difficult to diagnose. In a 65-year-old man with pain and swelling in the mandible, radiographs of the mandibular anterior region revealed cortical destruction and infiltration of the soft tissue by a mass lesion. Biopsy did not yield a definitive diagnosis. In accordance with a differential diagnosis of epithelial malignant tumor of the mandible, resection of the mass, bilateral superior neck dissection, and reconstruction with abdominal muscle grafts were performed. Histopathological study revealed asymmetric nuclei and cells with endoplasmic reticulum in which islands and cords of epithelial cells with low-grade cytological features were surrounded by a dense sclerotic stroma. Immunostaining yielded positive results for cytokeratin (CK) 5/6, CK19, and p63 and negative results for CK20. Because of the rarity of the disease process, clinicians, radiologists, and pathologists collaborated closely to establish a diagnosis of sclerosing odontogenic carcinoma.